Fighting for a Kingdom of God? The Role of Religion in the Ivorian Crisis - Johannes Vüllers (German Institute of Global and Area Studies (GIGA), 2011)
This paper analyzes the role of religion with regard to the violence experienced during the past 20 years in Côte d'Ivoire. It seeks to explain the differences in the level of violence over time by focusing on religion as an identity marker and as a social force that is mobilizable by religious and political actors. Religious identities were part of the growing in-/ out-group mechanism utilized in Côte d'Ivoire in the 1990s, while the political elites tried to politicize religion. In reaction to the violence and politicization, the religious elites founded an interreligious organization in the 1990s, and were successful in preventing a religious war.
Keywords: 300; religion; violence; peace; conflict; Côte d'Ivoire; Gewalt; Religion; Ideologie; Elite; Politischer Konflikt; Elfenbeinküste